Factors Affecting the Efficiency of AIS: An Empirical Study - Neogy, Taposh Kumar (Asian Accounting and Auditing Advancement, 2014)
An accounting Information System is an information system that identifies, classifies, processes, analyses and produces relevant financial-oriented meaningful information to support decision-making processes for the interested users. Accounting Information Systems is a set of capital and human resources within an organization, which is responsible for the preparation of financial information and also of the information obtained from the collection and process of transaction data. An accounting Information System is essential because it ensures that all levels of management get sufficient, adequate, relevant, and true information for planning and controlling activities of the organization. Adequate accounting information is essential for taking every effective decision-making process. The study shows that size of the company, earnings of the company, availability of trained accountants, internal control systems, the attitude of management, and organizational structure have a great effect on the efficiency of Accounting Information Systems and age of the company, resource of the company and rank of the responsible executive have a moderate effect on the efficiency of Accounting Information Systems of the sample mobile telecommunication companies.